THE BETEL NUT TRADITION IN THE ENGAGEMENT CEREMONY PROCESSION IN SUMBERDANTI VILLAGE FROM THE PERSPECTIVE OF 'URF - Sodiq, Ubaidillah; Ash Shiddiqi, Hasbi; Hasyim, Yanto (International Journal of Multidisciplinary Reseach, 2025)
The betel nut tradition in the engagement ceremony in Sumberdanti Village is a cultural heritage that remains preserved by the local community amidst the tide of modernization. This tradition not only serves as a symbol in the proposal procession but also serves as a means of respect, social communication, and affirmation of a man's seriousness in proposing to his future wife. This study aims to understand the meaning and position of the betel nut tradition from an Islamic legal perspective, specifically through the concept of 'urf'. The study used a qualitative method with a field approach, through interviews, observation, and documentation of the community members who practice the tradition. The results indicate that the betel nut practice has strong social and historical value, but from an Islamic legal perspective, it is classified as 'urf fasid', meaning a custom without an explicit basis in sharia law. Nevertheless, this tradition is still recognized as a form of local wisdom as long as it does not conflict with sharia principles. Therefore, the preservation of the betel nut tradition needs to be accompanied by a reinterpretation to align it with Islamic values and maintain its cultural identity in Sumberdanti Village.